2021
DOI: 10.35912/amor.v3i1.1171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recruitment and selection practices on organisational strategic goals

Abstract: Purpose: This study aimed at examining how recruitment and selection practices influence organisational strategic goals. Research methodology: A descriptive case study design was employed. Data was collected from 311 employees of Nestle Water Company who were randomly selected. Results: The study showed that screening affects profitability and market share positively though the effects were insignificant. The selection test on the other hand affects profitability both positively and significantly. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Adaptability is a leadership imperative and is linked to change, and the inability to adapt and change with time has dire consequences for leaders, managers, and organizations (Khatri, Dutta, & Raina, 2022;Rismansyah, Adam, Hanafi, & Yuliani, 2022). There is a demand for 21st-century organizations to face adaptive challenges (Bans-Akutey & Ebem, 2022;Hickman, 2010;Jayan, Bing, & Musa, 2016). Leadership trends in this new era have evolved and changed significantly (Ivancevich, Konopaske, & Matteson, 2014;Pang, 2013;Van Wart, 2013).…”
Section: Adaptability and Changementioning
confidence: 99%
“…Adaptability is a leadership imperative and is linked to change, and the inability to adapt and change with time has dire consequences for leaders, managers, and organizations (Khatri, Dutta, & Raina, 2022;Rismansyah, Adam, Hanafi, & Yuliani, 2022). There is a demand for 21st-century organizations to face adaptive challenges (Bans-Akutey & Ebem, 2022;Hickman, 2010;Jayan, Bing, & Musa, 2016). Leadership trends in this new era have evolved and changed significantly (Ivancevich, Konopaske, & Matteson, 2014;Pang, 2013;Van Wart, 2013).…”
Section: Adaptability and Changementioning
confidence: 99%
“…Crisis management revolves around the ability of organizations to minimize threats to survival (Alas et al, 2012;Strother, 2016;Zamoum & Gorpe, 2018). As studies have shown, the processes of recruitment into an organization and the level of members' involvement in the decisions have implications for its survival (Bans-Akutey et al, 2021;Pervin & Begum, 2022;Putra & Istiyani, 2022;Sastrawan et al, 2020). By extension, management of intra-party conflicts refers to the process of resolving conflicting interests within political parties.…”
Section: Conceptualizing Political Parties Intra-party Conflicts and ...mentioning
confidence: 99%
“…Every organization's main goal is to attain optimum productivity and achieve excellent performance in all operations. Therefore, management must establish an environment where people work productively to attain the organization's goals (Bans-Akutey & Ebem, 2022;Najam-us-Sahar, 2016). This suggests that a person's personality affects the productivity of a company.…”
Section: Introductionmentioning
confidence: 99%
“…The basic objective of every organization is to achieve ultimate performance and higher productivity (Bans-Akutey & Ebem, 2022;Bans-Akutey, Ohene Afriyie, & Tiimub, 2022;Prinhandaka, Rohman, & Wijaya, 2022). However, performance can be achieved when workers or employees accept their differences and work in teams (Gridwichai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%